Smart Protection for Enhancement of Stability Conditions of Distributed Generators - Siozinys, V.; Baranauskas, A. (Elektronika ir Elektrotechnika, 2012)
The transient stability of the dispersed generator were investigated. Generator is connected to the distribution network. The concept of smart protection is proposed. The smart protection coordination during the fault conditions was investigated. The dispersed generator transient stability with smart protection was investigated. The recommendations for generator protection coordination according to stability requirements are made. The investigation has showed, that the smart protections greatly increase generators stability margins. Ill. 6, bibl. 8, tabl. 2 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1056